Decolonizing racism in children's representations: learn to unlearn - Silvia Carbone (University of Bologna, 2023)
Within schools, children are called to learn from school books but above all from experiences lived in the classroom in a perspective of mutual recognition. Learning through experience means recognizing the materiality of cognitive processes and grasping the symbolic violence that fuels discrimination. At the same time, children in school are called to unlearn the weight of racist and colonialist discourses. But what practices to implement within the classroom to decolonize school programs, the contents of school disciplines and teaching methods? We analyzed the results of an educational project tested in a comprehensive school, which involved 30 students and 8 teachers. To verify the impact we asked ourselves: what can happen where this project has not been launched? Carrying out a counterfactual research, through the use of qualitative (focus group with teachers) and quantitative (structured and standardised questionnaire to students) tools, we evaluated the variation of objective outcomes, comparing the pre-project and post-project situation. What emerged from the research, with respect to the indicators observed, is that the project has produced a variation in the expected direction, of considerable size and statistically significant.